The Systematic Review of Lean Practices in India - Shankar, Udaya; Koushik, Rallabandi; Jacob, Jinu Sam; C, Athul; P V, Ranjith (Journal of International Conference Proceedings, 2024)
The systematic review of the literature examines studies on lean practices in India across a number of industries, providing insights into significant results, problems, and possibilities associated with the application of lean. Using a selection of relevant papers published in peer- reviewed journals, the study delivers results on lean performance evaluation, implementation challenges, enablers for lean practices, lean technology application, and sector-specific insights. The research identifies resistance to change and a lack of senior management support as hurdles, but it also underlines the importance of organizational culture, financial resources, and human resource management in supporting lean adoption. This study combines empirical information from a number of researches to give insights into tactics, techniques and best practices for implementing lean methodologies across diverse industry sectors in India. While these reviewed studies offer valuable knowledge, there are limitations to acknowledge which include sample size constraints; geographical focus as well as industry specific concerns. Future studies should focus on the dynamics of lean implementation in India taking account changing business environment within the country while considering emerging organizational management trends applies